EDUKASI PENGGUNAAN MEDIA SOSIAL BAGI REMAJA DI DESA MUARA BADAK ULU - Muh Shadiqul Fajri AF; Rahcmad Budi Suharto; Swadia Gandhi Mahardika; Akbar Lufi Zulfikar; Indra Maulana; Abiyajid Bustami (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
A socialization activity was conducted in Muara Badak Ulu Village with the aim of enhancing digital literacy and fostering critical and responsible attitudes toward social media usage. The event involved 50 participants, including junior high school students, senior high school students, and youth organization members. Through presentations, discussions, and case simulations, participants gained insights into the benefits of social media, potential risks such as digital addiction and the phenomenon of brain rot, as well as strategies for healthy social media engagement. The results revealed strong enthusiasm and critical awareness among participants regarding responsible digital behavior. One of the notable outcomes was the initiative to establish the Digital Literacy Community, which aims to continue digital literacy efforts in the local area. This activity demonstrates that community-based educational approaches can be effective in shaping positive digital behaviors among rural youth.